2002
DOI: 10.1046/j.1472-765x.2002.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification and characterization of an extracellular keratinase from Lysobacter NCIMB 9497

Abstract: Aims: The aim of this study was to determine the keratinolytic ability of a range of bacteria and subsequently, to characterize the keratinase showing the greatest biotechnological potential. Methods and Results: Nine bacteria, reported to produce extracellular proteases, were screened for production of keratinases. Of these, Lysobacter NCIMB 9497 exhibited the highest keratinolytic activity. The keratinase from this strain (M r 148 kDa) was purified and characterized. Optimum activity occurred at 50°C; no inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 12 publications
2
52
0
1
Order By: Relevance
“…Ultrafiltration has been applied in the purification of keratinases only intended to concentrate the enzyme for the next purification step [7,8,[27][28][29]. However, it is observed that the values found in the cited works are lower than those found in this study that use just one step.…”
Section: Concentration and Purification Of Keratinase Bymentioning
confidence: 64%
See 1 more Smart Citation
“…Ultrafiltration has been applied in the purification of keratinases only intended to concentrate the enzyme for the next purification step [7,8,[27][28][29]. However, it is observed that the values found in the cited works are lower than those found in this study that use just one step.…”
Section: Concentration and Purification Of Keratinase Bymentioning
confidence: 64%
“…e ultrafiltration step (MWCO of 10 kDa) achieved a purification factor of 1.8-fold and recovery of 69.3%. In the study of Allpress et al [28], the extracellular keratinase produced by Lysobacter NCIMB 9497 was purified for further characterization. In the ultrafiltration step (MWCO of 10 kDa), a purification factor of 2-fold was obtained.…”
Section: Concentration and Purification Of Keratinase Bymentioning
confidence: 99%
“…Broth cultures were carried out at various culture conditions such as temperature (10, 27, 37, 45°C), initial p H of the culture media (4,5,6,7,8,9), incubation time (1, 2, 3, 4, 5, 6, 7 days), to optimize the culture conditions for the production of extracellular proteases. To determine the effects of aeration, inoculated mediums were incubated at both stationary and shaking condition (100 rpm), keeping other experimental conditions at optimum.…”
Section: Optimization Of Culture Conditionsmentioning
confidence: 99%
“…Although protease can be obtained from several sources, including plant, animal and microorganisms, microbial proteases are preferred in view of their rapid growth, ease of cultivation purification and genetic manipulation. A large number of microorganisms have been reported for protease production [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…From this, a certain amount of poultry feather is converted to feather meal, which is used as animal feed stuff through extraordinary severe processes under high pressure and temperature [2]. Alternative methods, efficiently degrading intact feathers and overcoming the defects of prior processes, have been studied [3][4][5][6][7], though those were hardly applicable to practical degradation. One of the authors, KW, demonstrated the decomposition of hard-to-degrade animal proteins by moderately thermophilic bacteria showing optimum growth at around 60°C under aerobic conditions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%